Increasing Learning Activity Through Wordwall Media at Madrasah Ibtidaiyah Negeri 4 Tebo - sriwahyuningsih (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This research is motivated by the low learning activity of grade III students at Madrasah Ibtidaiyah Negeri 4 Tebo, which can be seen from the lack of participation in discussions, low courage to ask and answer, and lack of involvement in learning activities in the classroom. This research aims to increase student learning activity through the use of interactive learning media Wordwall. The method used is Classroom Action Research with the Kemmis and McTaggart models which includes planning, implementation of actions, observation, and reflection in two cycles. The research subjects amounted to 18 students consisting of 9 male students and 9 female students, while data collection was carried out through observation and documentation with quantitative descriptive analysis. The results of the study showed that the use of Wordwall was able to increase students' learning activity gradually, from an average of 33.83 in the pre-cycle stage to 48 and 56.83 in the first cycle, then increased again to 67.83 and 82 in the second cycle. Thus, it can be concluded that Wordwall media is effective in increasing student learning activity and creating more interesting, interactive, and fun learning at MIN 4 Tebo.